Make or Buy Decision Making with the Consideration of Inventory Cost - Teeravaraprug, Jirarat; Potcharathitikull, Tarathorn (International Journal of Engineering and Technology, 2018)
Make or buy decision making has recently received substantial theoretical and empirical attention. This paper integrates inventory cost in make or buy decision making. Many practitioners think that inventory cost is low when comparing with other types of costs. Therefore inventory cost seems to be neglect. This paper proposed two mathematical models of total costs in the cases of make and buy with the consideration of inventory costs. Based on the numerical example, it shows that the decision making may be changed with and without considering inventory costs. Further, considering variations of demand and purchase lead time, it is found that high demand variation tends to use buy option whereas high purchase lead time variation tends to use make option.Â Â